Liquid argon characterization of the X-ARAPUCA with alpha particles, gamma rays and cosmic muons. (4th November 2021) - Souza, H.V.; Segreto, E.; Machado, A.A.; Sarmento, R.R.; Bazetto, M.C.Q.; Paulucci, L.; Marinho, F.; Pimentel, V.L.; Demolin, F.L.; de Souza, G.; Fauth, A.C.; Ayala-Torres, M.A.
Abstract: The X-ARAPUCA device is the baseline choice for the photon detection system of the first far detector module of the DUNE experiment. We present the results of the first complete characterization of a small scale X-ARAPUCA prototype, which is a slice of a full DUNE module. Its total detection efficiency in liquid argon was measured with three different ionizing radiations: α particles, γ's and muons and resulted to be ∼2.2% when the active silicon photomultipliers were biased at +5.0 V of over voltage, corresponding to a Photon Detection Efficiency around 50% at room temperature. This value comfortably satisfies the requirements of the first DUNE far detector module (detection efficiency >2.0%) and allows to achieve an energy resolution comparable to the one achievable with the Time Projection Chambers for energies below 10 MeV, which is the region relevant for Supernova neutrino detection.